2022
DOI: 10.1021/acsomega.2c01162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gas Input Conditions and Ultrasound on the Dynamic Behavior of Flotation Bubbles

Abstract: Ultrasonic flotation is useful for fine low-rank coal purification; however, the efficiency of ultrasonic flotation still needs to be improved. Because the dynamic behavior of flotation bubbles has significant effects on their flotation efficiency, it was investigated under different gas input conditions with and without ultrasound using the volume of fluid method and h-speed imaging. The results indicated that the gas input method can influence the final kinetic behavior of the flotation bubbles by changing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…It was found that ultrasonic flotation was more effective with the shallow froths due to an increase in the bubble coalescence. Figure 22 illustrates the principle of bubble aggregation in an ultrasonic field [148]. Mao et al [148] employed ultrasonic pretreatment (UPT) and simultaneous treatment (UST) with different ultrasonic powers to float coal.…”
Section: Coalescencementioning
confidence: 99%
See 1 more Smart Citation
“…It was found that ultrasonic flotation was more effective with the shallow froths due to an increase in the bubble coalescence. Figure 22 illustrates the principle of bubble aggregation in an ultrasonic field [148]. Mao et al [148] employed ultrasonic pretreatment (UPT) and simultaneous treatment (UST) with different ultrasonic powers to float coal.…”
Section: Coalescencementioning
confidence: 99%
“…Figure 22 illustrates the principle of bubble aggregation in an ultrasonic field [148]. Mao et al [148] employed ultrasonic pretreatment (UPT) and simultaneous treatment (UST) with different ultrasonic powers to float coal. They found that the flotation of coal was improved when using ultrasonic treatment through the combined effect of cavitation and acoustic radiation force.…”
Section: Coalescencementioning
confidence: 99%